Movie as a media in improving understanding the cooperative principles and the politeness principles - Sentana, Yuli Mahmudah; Samsul, Samsul; A.R.G., Muh. Yazid (Diksi, 2022)
The background of this study is the use of the RRRrrr!!! Movie by Alain Chabat as learning media in pragmatic courses, especially on the cooperative principle and the politeness principle. The use of this movie is based on the existence of 51 violations of the cooperative principle and the politeness principle in RRRrrr!!! movie. This research is a mixed research that applies qualitative research and quantitative research. The results showed that the use of this movie increased student learning outcomes by 40.26%. Student responses are also enthusiastic with the results of the 100% questionnaire using this movie as a learning medium. The results of the questionnaire also explained that the examples in the movie were very helpful in understanding the cooperative and politeness principle.  Keywords: the cooperative principle, the politeness principle, movie as learning media